Electrochemical Transformation of Metal Organic Framework into Ultrathin Metal Hydroxide-(oxy)hydroxide Nanosheets for Alkaline Water Oxidation - Singh B.; Prakash O.; Maiti P.; Indra A. (My University, 2025)
Electrochemical water oxidation requires a highly active electrocatalyst system with improved catalytic activity, high mechanical stability, and strong catalyst-support interactions. In this respect, a unique and facile method has been developed for the synthesis of ultrathin Fe-Co(OH)2-Co(O)x(OH)y nanosheets from self-supported Prussian blue analogues by chronoamperometric method. High electrochemical surface area, improved electronic conductivity, enhanced mechanical stability, and atomic level thickness (3 nm) of the self-supported ultrathin nanosheets provided the boost for alkaline water oxidation. The ultrathin Fe-Co(OH)2-Co(O)x(OH)y nanosheets demonstrated 10 mA cm-2 current density at only 250 mV overpotential for alkaline water oxidation. The ultrathin nanosheets also showed 24 h continuous oxygen evolution under chronoamperometric condition without losing the initial activity. Copyright © 2020 American Chemical Society.